The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3766/jaaa19017
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Head Circumference and Age in the Prediction of the Real-Ear-to-Coupler Difference (RECD)

Abstract: Background: Pediatric hearing instrument fitting is optimally performed with individually obtained realear-to-coupler difference (RECD) measurements. If these measurements cannot be obtained, predictedvalues based on age are used. Recent evidence obtained from children aged 3–11 years suggests thathead circumference (HC) may be a viable alternative or addition to age for use in RECD prediction.Purpose: The purpose of the present study was to determine if HC can be used to predict RECDs ininfants, children, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…This could be due to differences in the volume of the ear canals of DHH children from Eastern and Western countries. As previous studies have suggested, individual variations in RECDs can range from ±5.6 dB at 500 Hz to ±10.9 dB at 6000 Hz compared to reference values, and these variations may be influenced by factors such as head circumference and ear canal growth [18,20,21]. In the present study, we observed higher measured RECDs at low frequencies and smaller measured RECDs at high frequencies compared to the reference values, which could be attributed to differences in the ear canal geometry of DHH children from Eastern and Western countries.…”
Section: Discussionmentioning
confidence: 95%
“…This could be due to differences in the volume of the ear canals of DHH children from Eastern and Western countries. As previous studies have suggested, individual variations in RECDs can range from ±5.6 dB at 500 Hz to ±10.9 dB at 6000 Hz compared to reference values, and these variations may be influenced by factors such as head circumference and ear canal growth [18,20,21]. In the present study, we observed higher measured RECDs at low frequencies and smaller measured RECDs at high frequencies compared to the reference values, which could be attributed to differences in the ear canal geometry of DHH children from Eastern and Western countries.…”
Section: Discussionmentioning
confidence: 95%